Identifying a process in victims girls/boys of gender violence and the treatment guidelines - Ramírez S., Natalia (2012)
It is about a process to identify the gender violence of girls/boys victims and the treatment guidelines as a theoretical view that examine the problem from conscious and unconscious aspects; there are two clinical examples and that are showed in recent researches that the matter gives us relevant data. The objectives are centered in to know the preventive aspects and the most effective intervention to contributethrough the diffusion of that knowledge and the healthy development of gender violence in minor victims.